2014
DOI: 10.1049/iet-smt.2013.0262
|View full text |Cite
|
Sign up to set email alerts
|

Moisture and electrical discharges effect on naphthenic mineral oil properties

Abstract: The physicochemical properties of three transformer mineral oils of different levels of degradation, resulting from exposure to moisture and electrical discharges, are investigated. The first oil is new and untreated whereas the second is taken from a transformer after one year of normal operation; and the third oil is extracted from a 15-year-old operating transformer. The considered parameters are breakdown voltage, dielectric constant ε r , dissipation factor (tan δ) and resistivity. Isothermal charging cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The reduction in water content with the application of discharges is mainly due to the evaporation of water traces that are present in the zone of discharge occurrence. A similar result has been reported in mineral oil submitted to discharges of the same energy level [30].…”
Section: Resultssupporting
confidence: 88%
“…The reduction in water content with the application of discharges is mainly due to the evaporation of water traces that are present in the zone of discharge occurrence. A similar result has been reported in mineral oil submitted to discharges of the same energy level [30].…”
Section: Resultssupporting
confidence: 88%
“…The presence of water content (Eq. (7)) in the transformer oils negatively influences the dielectric characteristics of this insulating liquid and also the insulating solid (paper) [20]. The solubility of water in oil depends essentially on three factors: the temperature, the type of oil (mineral or vegetable), and its condition (new or aged).…”
Section: Methodsmentioning
confidence: 99%
“…According to an investigation by Ngai and Roland (), there is a correlation between dielectric loss and the chemical structure of polymers. In a different study, the effect of different types of mineral oils on electrical properties was investigated by Toudja et al (). The authors found that the relative permittivity of a fluid depends on the internal structure of the oil and its impact on polarity.…”
Section: Introductionmentioning
confidence: 99%
“…152 (Zahn et al, ), molecular and supermolecular structures of insulating liquids have been listed as one of the factors that influence the dielectric strength. From these studies, it becomes apparent that indeed molecular structures had an influence on the electrical properties of insulating liquids (Forster et al, ; Ngai and Roland, ; Nitta and Aihara, ; Toudja et al, ; Zahn et al, ).…”
Section: Introductionmentioning
confidence: 99%